2021
DOI: 10.1007/s41999-021-00512-5
|View full text |Cite
|
Sign up to set email alerts
|

Under-triage of older trauma patients in prehospital care: a systematic review

Abstract: Background It is argued that many older trauma patients are under-triaged in prehospital care which may adversely affect their outcomes. This systematic review aimed to assess prehospital under-triage rates for older trauma patients, the accuracy of the triage criteria, and the impact of prehospital triage decisions on outcomes. Methods A computerised literature search using MEDLINE, Scopus, and CINHAL databases was conducted for studies published between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…The under triage of geriatric trauma patients has been demonstrated numerous times. [12][13][14] Reasons for under triage are likely multifactorial, including comorbidities, medications blunting physiologic response, and frailty. Standard trauma scoring systems and triage guidelines may not be sensitive enough for this population.…”
Section: Discussionmentioning
confidence: 99%
“…The under triage of geriatric trauma patients has been demonstrated numerous times. [12][13][14] Reasons for under triage are likely multifactorial, including comorbidities, medications blunting physiologic response, and frailty. Standard trauma scoring systems and triage guidelines may not be sensitive enough for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported in other economically developed nations. [3][4][5][6] There is evidence that the emerging cohort are at greater risk of being under-triaged, 7,8 are less likely to receive care at a higher-level trauma facility, 9,10 are more likely to be treated by junior clinicians, more likely to have longer waits for CT scans, and are less likely to be transferred to a neurosciences unit. 11,12 A recent systematic review has demonstrated that higher-level trauma centres are associated with lower mortality than lower-level trauma centres in patients with major trauma (adjusted odds ratio, AOR, 0.77; 95% CI 0.69-0.87).…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been reported in other economically developed nations. 36 There is evidence that the emerging cohort are at greater risk of being under-triaged, 7,8 are less likely to receive care at a higher-level trauma facility, 9,10 are more likely to be treated by junior clinicians, more likely to have longer waits for CT scans, and are less likely to be transferred to a neurosciences unit. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…It has been described repeatedly how current triage methods produce inadequately low results in older patients [9][10][11]. This risk of underestimation of urgency translates into longer waiting times and a higher risk of adverse outcomes due to the delay [12][13][14]. Therefore, despite the usefulness of triage tools, we recognize inconsistencies and notable room for improvement that force us to be cautious in their interpretation and to consider their critical review.…”
mentioning
confidence: 99%
“…Relevant to geriatric medicine is the fact that all triage methods show, in older adults, lower levels of efficacy than in the global population [9][10][11]. In consequence, old patients are at greater risk of being assigned an inappropriately low triage level, which translates into longer waiting times and a higher risk of adverse outcomes [12][13][14]. The poorer performance of traditional triage tools in the older population, which underestimate the urgency [23,24], is often explained by a high frequency of atypical presentations of acute conditions, due to associated factors, such as polypharmacy, delirium or dementia that may cloud the clinical presentation of diseases [25], by the non-inclusion in scores of agecorrection factors of vital signs, and by ageism, which can also contribute to poor care and lack of compliance with evidence-based practices [26].…”
mentioning
confidence: 99%